A syndemic of psychiatric morbidity, substance misuse, violence, and poor physical health among young Scottish men with reduced life expectancy. (September 2021) - Coid, Jeremy; Zhang, Yingzhe; Bebbington, Paul; Ullrich, Simone; de Stavola, Bianca; Bhui, Kamaldeep; Tsai, Alexander C.
Abstract: Background: Scotland has the shortest life expectancy in Western Europe, driven by high rates of cancer, suicides, alcohol-related causes and drug-related poisonings. These disparities cannot be explained solely by socioeconomic deprivation. Our aim was to investigate whether a syndemic in a socioeconomically deprived area of Glasgow might account for premature mortality among men. Methods: We analysed data from two cross-sectional population surveys: a national sample of 1916 British men and another of 765 men in Glasgow East. The survey included men aged 18–34, and was undertaken in 2011 to study correlates of violence. Questionnaires covered current physical health, psychiatric symptoms, substance misuse, and crime and violence. Syndemic components were identified using confirmatory factor analysis. Associations and synergistic interactions between these variables and health status were estimated using logistic regression. Results: An aggregation of multiple health conditions and health-related behaviours was found in Glasgow East. A syndemic model of joint effects, adducing a four-component latent variable (violence, substance dependence, psychiatric morbidity and a diathesis of biological/behavioural risk) showed synergy between components and explained persistent disparities in poor physical health/chronic health conditions. Effect modification was found between the general syndemic factor and contextual variables at individual and social environmental level according to location. Conclusions: Syndemic effects from synergistic interactions were confirmed between psychiatric morbidity, substance misuse, violence, and biological/behavioural risk for physical health. A hypothetical model was developed to explain how the syndemic leads to potentially life-threatening risks to young men, both currently and as precursors of physical health conditions which may shorten their lives in the future. Highlights: Scotland has the shortest life expectancy in Western Europe, especially among men in areas of Glasgow. This has not responded to Public Health interventions. A syndemic was identified among young men with synergism between violence, substance misuse, biological/behavioural physical health risks, and psychiatric morbidity. Synergistic interactions between components of the syndemic may result in precursors of multiple physical health conditions which will shorten men's lives in the future.